Environmental Crystalline Silica Exposure in Wisconsin : a Risk Assessment and Evaluation - Nelson, Gregory T.; Fay, James; Kleist, Andrew (My University, 2012)
As many new and proposed sand mines and processing plants in Wisconsin add to the 2,300 current industrial sources, public exposure to small particles including respirable crystalline silica (RCS) is increasing rapidly. RCS occupational studies have documented causation of silicosis, tuberculosis, kidney disease and lung cancer. Exposure to the public is regulated in five states, but not in Wisconsin where the Department of Natural Resources has determined that not enough data exist to establish an exposure standard. This study used approaches in Gaussian dispersion modeling, aerosol and gravimetric measurements, and citizen monitoring to assess PM 10, PM 4, PM 2.5 and RCS levels before and after construction of a large sand processing plant to assess potential health risks in a Wisconsin community.
Color poster with text, images, graphs, and tables.
Keywords: Silica--Wisconsin; Silica--Health aspects; Silica dust--Wisconsin; Silica dust--Health aspects; Posters